Acute Myeloid Leukemia with complex hyperdiploid karyotype: A Case Report - Pais, Anurita; Pande, Shailesh; Pradhan, Gauri; Tharali, Akshay; Patil, Smita; Parab, Chaitali (Annals of Pathology and Laboratory Medicine, 2018)
Hyperdiploidy in acute myeloid leukemia (AML) forms a subset of complex karyotype, which needs to be cytogenetically characterized so as to accurately determine its prognostic factor. The following study, involves the case of 54 year old female patient diagnosed with denovo acute myeloid leukemia by cytomorphological and immune-phenotype studies. Cytogenetic analysis revealed a high hyperdiploid karyotype with a modal chromosome number ranging from 51 54 with the gain of chromosomes 8, 9, 11, 12 and 19 and also monosomy for chromosome 5. It also revealed other chromosomal abnormalities such as formation of derivative chromosome 10, isochromosome 21 and presence of a marker chromosome. Present case reinforces the importance of cytogenetic categorization of an adverse-risk complex aberrant karyotype to stratify patients to individual optimized treatment strategies other than standard treatment in order to achieve good treatment outcome.